Smart Helmet Based on Microcontroller for Motorcyclists - Prananda Asri, Rehan; Sardi, Juli (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
Motorcycles are one of the most popular types of transportation used by people in Indonesia. However, the use of motorcycles has its own risks and problems such as the high number of motorcycle accidents. Human error is one of these factors, for example not paying attention to the distance with the vehicle in front and using a smartphone while driving. In addition, the problem of helmet theft is one of the factors that reduce driving safety. This research aims to create a smart helmet that helps reduce the use of smartphones while driving, provide safe distance notifications between vehicles, and create a tracking system in case of theft. This research uses hardware which includes nodemcu esp32, hc-sr04 sensor, neo 6m gps module, and max98357 i2s audio amplifier module and software including telegram for notification and control and programming using ardiuno IDE. After the experiment, all components and systems of this smart helmet are able to work as expected and in line with the research objectives. The application of this smart helmet can help overcome the use of smartphones while driving, know the safe distance with the vehicle in front and assist in finding a helmet in the event of theft.